Daylength effects on stress and fear responses in broiler chickens - Idrus, Zulkifli; Abdullah, Rasedee; O., Nor Syaadah; Mat Taib, Che Norma (Asian-Australasian Association of Animal Production Societies, 1998)
Heterophil (H) to lymphocyte (L) ratios and durations of tonic immobility (TI) were measured to assess stress and fear responses, respectively, in broiler chickens provided either 12 h of natural lighting (12L) or 12 h natural lighting and 12 h of supplementary lighting (24L). Birds illuminated 24L had greater H/L ratios and TI durations than their 12L counterparts. Neither age, sex nor cage level had significant effect on TI reactions.